Effect of socio-economic factors in utilization of different healthcare services among older adult men and women in Ghana - Saeed, B.I.I.; Yawson, A.E.; Nguah, S.; Agyei-Baffour, P.; Emmanuel, N.; Ayesu, E. (BioMed Central Ltd., 2016)
Background: The older adult population is increasing all over the world. In sub-Saharan Africa, due to poverty and low policy coverage, older adults are not well catered for. The effect of socio-economic inequality in the use of healthcare services among older adult men and women in Ghana was investigated in this paper. Methods: The data employed in the study were drawn from Global Ageing and Adult Health survey SAGE Wave 1 Ghana and was based on the design for the World Health Survey 2003, SAGE Wave 0, Ghana. The survey was conducted in 2007-2008 and collected data on socio-economic characteristics and other variables of the 5573 individuals interviewed. Results: Using generalized logit model, the study found that health status is a very strong determinant of the type of healthcare services preferred by older adults Ghanaians. Men with higher income preferred the private health facilities, while those who completed tertiary education, those with health insurance and those who self-rated their health as very bad, bad or moderate preferred public facility. Self-employed men and those in informal employment, preferred other health facilities outside the formal public health service. Women with primary and secondary education, preferred the private health facilities. Women with health insurance, those in middle and upper class income quintiles or those with self-rated bad and moderate health status or being relatively younger preferred the public facility to other health services. Self-employed women and those in informal employment preferred traditional treatment. In Ghana, there are important socio-economic gradients in the use of some healthcare services. In both sexes, those without insurance and rural residents preferred the pharmacy and traditional treatment. Conclusion: These differences may be due to socio-economic inequities but could also indicate that the existing health facilities are not always used in an optimal way. Patient factors may be equally important as supply factors in explaining the differential use of health services. The public health systems in Ghana still have a major role in improving the health of older adults. National commitments in providing basic essential infrastructure and personnel to health centres for the citizenry is imperative. Policy readjustment of the national health insurance scheme to make it truly accessible to the aged is essential.
Keywords: Generalized logit; Ghana; Healthcare utilization; Socio-economic inequities